Influence of chronic exercise on carotid atherosclerosis in marathon runners. Issue 2 (14th February 2014) - Taylor, Beth A; Zaleski, Amanda L; Capizzi, Jeffrey A; Ballard, Kevin D; Troyanos, Christopher; Baggish, Aaron L; D'Hemecourt, Pierre A; Dada, Marcin R; Thompson, Paul D
Abstract : Objectives: The effect of habitual, high-intensity exercise training on the progression of atherosclerosis is unclear. We assessed indices of vascular health (central systolic blood pressure (SBP) and arterial stiffness as well as carotid intima-medial thickness (cIMT)) in addition to cardiovascular risk factors of trained runners versus their untrained spouses or partners to evaluate the impact of exercise on the development of carotid atherosclerosis. Setting: field study at Boston Marathon. Participants: 42 qualifiers (mean age±SD: 46±13 years, 21 women) for the 2012 Boston Marathon and their sedentary domestic controls (46±12 years, n=21 women). Outcomes: We measured medical and running history, vital signs, anthropometrics, blood lipids, C reactive protein (CRP), 10 years Framingham risk, central arterial stiffness and SBP and cIMT. Results: Multiple cardiovascular risk factors, including CRP, non-high-density lipoprotein cholesterol, triglycerides, heart rate, body weight and body mass index (all p<0.05), were reduced in the runners. The left and right cIMT, as well as central SBP, were not different between the two groups (all p>0.31) and were associated with age (all r≥0.41; p<0.01) and Framingham risk score (all r≥0.44; p<0.01) independent of exercise group (all p>0.08 for interactions). The amplification of the central pressure waveform (augmentation pressure at heart rate 75 bpm) was also not different between the two groups (p=0.07) but was related to age (p<0.01) and group (p=0.02) in a multiple linear regression model. Conclusions: Habitual endurance exercise improves the cardiovascular risk profile, but does not reduce the magnitude of carotid atherosclerosis associated with age and cardiovascular risk factors.